ROLE OF GRANISETRON IN MINIMISING USE OF MEPERIDINE AS A RESCUE DRUG FOR POST SPINAL SHIVERING - Wahid, Maheen; Ali, Shabana; Noor, Mudassar; Farhat, Kulsoom (Journal of Ayub Medical College Abbottabad, 2023)
Background: Shivering is one of the most common adverse outcomes associated with the administration of spinal anaesthesia, which, when clinically relevant, leads to numerous detrimental effects on the human body. Hence, its management becomes imperative. Meperidine, an opioid analgesic, is the drug of choice for this condition. However, the use of meperidine is controversial, as it carries the devastating adverse effect of respiratory depression. We explored the role of granisetron, a 5HT3 antagonist and a commonly used antiemetic premedication, in minimising the incidence of post-spinal shivering and decreasing the use of meperidine as a rescue drug. Methods: Overall, 160 parturient patients, between the ages 18-50, undergoing uncomplicated, elective caesarean section, were enrolled in the study, and randomized into two groups with 80 participants each: Group A received 3ml of normal saline, and Group B was administered 3 mg granisetron,15 minutes prior to spinal anaesthesia institution. Incidence of clinically relevant shivering (score of 3 or more) was noted, and it was recorded whether meperidine was used or not. Results: 67.5% of participants in Group A, and 32.5% of patients in Group B, experienced clinically relevant shivering, with 62.5% of patients in Group A and 28.75% in Group B warranting the use of meperidine. There was a statistically significant difference between the two groups in terms of incidence of clinically relevant shivering, and meperidine consumption (p-value <0.001). Conclusion: Premedication with 3 mg granisetron effectively attenuates the occurrence of post-spinal shivering and, hence, lowers the requirement of meperidine as rescue medication.